Does network matter in international expansion? Evidence from Italian SMEs - Antonia Rosa Gurrieri; Luca Petruzzellis (Fondazione Eni Enrico Mattei (FEEM), 2008)
In order to face the new competitive scenario, Apulian textile firms are involved in a process of change and are trying to adopt a networking approach in analysing the international propensity of SMEs. The case of the textile network in Apulia has been analysed using a semi-structured questionnaire submitted to a sample of family businesses in order to verify the influence of network on their internationalisation process. The contribution that the network can give to the single firm in its internationalisation process depends also on the level of cooperation in the network. In fact, relationships - at least dual vertical relationships - are the key to overcoming size limit and providing value to all the partners involved. The research attempted to offer a better academic understanding of the role of network in international competitive advantage. Future research should be based on cross countries analysis, in order to determine whether or not the set of internal determinants of internationalisation propensity remain stable from one country to another. The findings should also be useful to local governance for a better understanding of the network phenomenon in order to develop appropriate programmes for training and supporting SMEs in the global market. This paper provides a wide analysis of the network role in the internationalisation process in a low technology sector.
Keywords: L2; D85; 330; Internationalisation Strategies; Network Approach